Folkcommunication in Latin America (Revista Internacional de Folkcomunicação, 2018)
This article discusses the cultural formation and processes of extermination of original peoples in Brazil, as well as the trajectory of cultural studies that, since the nineteenth century, from the contributions of several researchers, seek to understand the culture of the people. It presents, therefore, antecedents of the studies of folkcommunication and connections with the culture and the research in Latin America. The work originated in a lecture held at the XVIII Conferência Brasileira de Folkcomunicação, in Recife in 2017. Culture; Anthropology: Folkcommunication; Latin America.